IMPROVING STUDENTS™ SPEAKING ACHIEVEMENT THROUGH PUBLIC SPEAKING TASKS - Sari, Puspita (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study deals with improving students™ speaking achievement through public speaking tasks. This study was conducted by using classroom action research. The subject of the research was class XI AP2 SMK BM Taman Siswa Lubuk Pakam consisted of 32 students.  The research was conducted in two cycles and every cycle consisted of four meetings. The instruments for collecting data were oral test for quantitative data and diary notes and interview for qualitative data. Based on the oral test scores, students™ score kept improving in every test. In the orientation test, the mean score was 55.9, in the first competence test, the mean score was 64.4 and in the second competence test, the mean score was 73. The improvement also can be seen from the percentage of the students™ speaking achievement, in the orientation test only 3.13% (one student) got 65 points. In the first competence test 65.63% (twenty one students) got 65 %. It means there was an improvement about 62.5%. In the second competence test 93.75% (thirty students) got 65 points. The improvement was 31.25%. It can be concluded that public speaking tasks could improve students™ speaking achievement.   Key Words: Speaking, Achievement, Public Speaking, Tasks